Moringa Oleifera (MO) seed shell based adsorbent synthesis for CO2 capture - Tahreen, Amina; Jami, Mohammed Saedi; Ali, Fathilah; Mohammad, Zahangir Alam (2022)
Moringa Oleifera (MO) seeds are widely explored plant for bio coagulant extraction generating waste seed shells. This study aims to synthesize natural adsorbent from MO seed shells with potassium hydroxide (KOH) and test its ability for CO2 adsorption. After oven drying, chemical activation was carried out with impregnation ratios of 1:1, 2:1 and 3:1. Next, the following thermal activation will be carried out through microwave assisted heating instead of conventional muffle furnace, due to its potentially simpler, faster and low cost adsorbent production. Researchers typically found optimum values for activation time within the range 30 to 70 minutes of microwave radiation time, while the effect of power (W) was within 300 to 600 W. The resulting activated carbon after cooling and washing, will be characterized for Brunauer, Emmett and Telle (BET) analysis for measuring the surface area of the activated carbon. The chemical structure of the porous adsorbent will be further observed with Fourier Transform Infrared Radiation (FTIR), X-ray Diffraction (XRD) and Scanning Electron Microscope (SEM) analyses along with its ability for CO2 adsorption. These analyses will give an understanding of the formation of porosity in the adsorbent surface that contributes to carbon capture. The natural adsorbent is expected to be potentially better at carbon capture due to thermal activation at a more controlled microwave heating environment with N2 supply.